Harvesting and marketing potentiality of Chiraito (Swertia chirayita), Amriso (Thysanolaena maxima), and Timur (Zanthoxylum armatum) in western mid hills of Nepal - Bolakhe, Sandesh; Ghimire, Pramod; Kafle, Gandhiv (Journal of Agriculture and Natural Resources, 2024)
This study carried out in April, 2016 assesses the market potentiality and different factors affecting the collection of non-timber forest products (NTFPs), mainly Chiraito (Swertia chirayita), Amriso (Thysanolaena maxima), and Timur (Zanthoxylum armatum) (CAT) found in the Panchase region of western Nepal. Three communities Bagefadke (Syangja), Ramjha (Parbat), and Bhadaure Tamagi (Kaski) of Panchase region were selected as the study site. Data were collected using a structured schedule interview with 105 randomly selected households (HHs) and included information collected from key informants (KIIs) and focus group discussions (FGDs). Collection of CAT varied across the HHs; on average they collected 0.38 kg of Chiraito, 7.28 Bhari Amriso, and 0.62 kg Timur seasonally. The findings revealed that age, large family size, illiterate peoples, and near users were more likely to collect CAT. Similarly, sex was found to significantly reduce the activity of collection and trade of NTFPs. Walking distance to the resource significantly increases the favor of collection indicating that the valuable CAT collected are from near locations. While the positive relationship between family size, distance from home, and collection (p